Employment Legal System for TKI in Legal Protection - Miftia Nur Annisa; Rika Maryani; Aris Prio Agus Santoso (Proceeding International Conference Restructuring and Transforming Law, 2022)
The purpose of this research is to find out how the existence of TKI is in the protection of labor law, because along with the progress of the times (globalization era), problems in the field of employment are also increasing, especially if it is associated with other aspects such as economic, social and political. However, the basic problems in this field still do not deviate from the classic problems, namely the “master-worker” relationship, strikes and dismissals, and rights and obligations. Workers and employers in their respective positions have rights and obligations. However, in this case, it is the workers who need to be protected and guaranteed by law in exercising their rights. In the field of employment, these guarantees often include economic guarantees.